Effectiveness of pedalling retraining in reducing bilateral pedal force asymmetries - Bini, R. R.; Jacques, T. C.; Carpes, F. P.; Vaz, M. A. (Journal of Sports Sciences, 2017)
Previous studies have been limited to describe asymmetries during pedalling and suggest possible repercussion on performance and/or injury risks. However, few studies have presented strategies to mitigate asymmetries. The purpose of this study was to assess the effectiveness of a pedalling retraining intervention to reduce bilateral pedal force asymmetries. Twenty cyclists were assessed and 10 enrolled in a pedalling retraining method receiving visual and verbal feedback of pedal forces. The asymmetry index was computed for comparison of bilateral peak pedal forces and used during retraining (12 trials at 70% of peak power). Significantly larger asymmetry was observed for asymmetrical cyclists at the first three trials (P < 0.01 and ES = 1.39), which was reduced when post-retraining was compared to measures from symmetrical cyclists (P = 0.69 and ES = 0.18). Cyclists with larger asymmetry (>20%) in bilateral pedal forces reduce their asymmetries using sessions of pedalling retraining and achieve asymmetry indices similar to symmetrical cyclists.